1986
DOI: 10.1007/bf02213962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthelmintics onHaemonchus contortus (Nematoda: Trichostrongylidae)

Abstract: The review summarizes and evaluates recent information about the effects of anthelmintics on Haemonchus contortus. The topic is discussed under the headings effects of drugs on the absorptive surfaces, effects of drugs on metabolism, effects of drugs on the neuromuscular system, effects of drugs on developmental stages, anthelmintic efficacy, and resistant strains. Possible future lines of work are suggested in the conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Due to muscular discoordination/paralysis food swallowing and movement through the digestive system is stopped. The parasites enter the state of starvation and energy deprivation and thus, unable to survive inside the host (Kaur and Sood, 1982;Opperman and Chang, 1992). The antiparasitic activity of A. sativum may also be attributed to the sulfur containing compounds (e.g., ajoene and allicin) which can possibly form disulphide bonds with free thiol groups, and thus, inhibit enzymes or other proteins, which are important for survival of the parasite (Krstin et al, 2018).…”
Section: Pharmacological Actionmentioning
confidence: 99%
“…Due to muscular discoordination/paralysis food swallowing and movement through the digestive system is stopped. The parasites enter the state of starvation and energy deprivation and thus, unable to survive inside the host (Kaur and Sood, 1982;Opperman and Chang, 1992). The antiparasitic activity of A. sativum may also be attributed to the sulfur containing compounds (e.g., ajoene and allicin) which can possibly form disulphide bonds with free thiol groups, and thus, inhibit enzymes or other proteins, which are important for survival of the parasite (Krstin et al, 2018).…”
Section: Pharmacological Actionmentioning
confidence: 99%
“…Adult H. contortus lives in an environment with low oxygen tension and so the high rate of fatty acid synthesis relative to other lipid components might be related to the need to provide NADP for dehydrogenases of the pentose phosphate pathway. Enzymes of the pentose phosphate pathway have been demonstrated in the adult H. contortus (12). Also, since it has been demonstrated to synthesize long-chain and branched fatty acids from glucose, WARD (24) suggested that the biological functions of long-chain fatty acids and branched acids, most rapidly synthesized by adult H. contortus, are to assist the worm in lysing the RBC of its host.…”
Section: 560mentioning
confidence: 99%